"Chrono-functional milk": The difference between melatonin concentrations in night-milk versus day-milk under different night illumination conditions. (26th November 2015) - Asher, A.; Shabtay, A.; Brosh, A.; Eitam, H.; Agmon, R.; Cohen-Zinder, M.; Zubidat, A.E.; Haim, A.
Abstract : Pineal melatonin (MLT) is produced at highest levels during the night, under dark conditions. We evaluated differences in MLT-concentration by comparing daytime versus night time milk samples, from two dairy farms with different night illumination conditions: (1) natural dark (Dark-Night); (2) short wavelength Artificial Light at Night (ALAN, Night-Illuminated). Samples were collected from 14 Israeli Holstein cows from each commercial dairy farm at 04:30 h ("Night-milk") 12:30 h ("Day-milk") and analyzed for MLT-concentration. In order to study the effects of night illumination conditions on cows circadian rhythms, Heart Rate (HR) daily rhythms were recorded. MLT-concentrations of Night-milk samples from the dark-night group were significantly ( p < 0.001) higher than those of Night-illuminated conditions (30.70 ± 1.79 and 17.81 ± 0.33 pg/ml, respectively). Interestingly, night illumination conditions also affected melatonin concentrations at daytime where under Dark-Night conditions values are significantly ( p < 0.001) higher than Night-Illuminated conditions, (5.36 ± 0.33 and 3.30 ± 0.18 pg/ml, respectively) . There were no significant differences between the two treatments in the milk yield and milk composition except somatic cell count (SCC), which was significantly lower ( p = 0.02) in the Dark-Night group compared with the Night-Illuminated group. Cows in both groups presented a significant ( p < 0.01) HR daily rhythm, therefore we assume that in the night illuminated cows feeding and milking time are the "time keeper", while in the Dark-night cows, HR rhythms were entrained by the light/dark cycle. The higher MLT-concentration in Dark-night cows with the lower SCC values calls upon farmers to avoid exposure of cows to ALAN. Therefore, under Dark-night conditions milk quality will improve by lowering SCC values where separation between night and day of such milk can produce chrono-functional milk, naturally rich with MLT.